2019
DOI: 10.1111/dme.13926
|View full text |Cite
|
Sign up to set email alerts
|

Women's views on lifestyle changes to reduce the risk of developing Type 2 diabetes after gestational diabetes: a systematic review, qualitative synthesis and recommendations for practice

Abstract: Aims After gestational diabetes, many women exhibit behaviours that increase their risk of developing Type 2 diabetes. We aimed to systematically synthesize the literature that focuses on the views of women with a history of gestational diabetes on reducing their risk of developing diabetes postpartum through lifestyle and behaviour changes. Methods We identified qualitative studies that examined the views of women with a history of gestational diabetes towards healthy eating and physical activity, Type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 49 publications
5
126
0
3
Order By: Relevance
“…Our meta-analysis did not find a significant effect on other intervention characteristics such as format of delivery, intensity or duration [6]. This aligns with Dennison et al who described mixed responses on these characteristics [1]. The Consolidated Framework for Implementation Research (CFIR) [7] describes interventions as having core components and adaptable periphery.…”
Section: Competing Interestssupporting
confidence: 81%
See 2 more Smart Citations
“…Our meta-analysis did not find a significant effect on other intervention characteristics such as format of delivery, intensity or duration [6]. This aligns with Dennison et al who described mixed responses on these characteristics [1]. The Consolidated Framework for Implementation Research (CFIR) [7] describes interventions as having core components and adaptable periphery.…”
Section: Competing Interestssupporting
confidence: 81%
“…We read with interest the study by Dennison et al [1] which provided a qualitative synthesis on the facilitators and barriers to lifestyle changes from the perspective of women with recent gestational diabetes (GDM). We would like to provide some additional insights from our own work.…”
Section: Competing Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with a history of GDM experience substantial barriers to adopting healthy lifestyle behaviours, including carer responsibilities, poor timing of education and fragmented care as well as additional cultural barriers for women born overseas [ 54 , 55 ]. While intensive lifestyle interventions are effective at delaying or preventing progression to diabetes [ 12 ], such interventions require extensive resources and support.…”
Section: Discussionmentioning
confidence: 99%
“…22 Systematic reviews have identified the need for specific, tailored, and empathic conversations about the complexities of managing GDM in the context of everyday life and available supports. 9,20,21 To date, however, findings have not fully characterized how women's perceptions, shaped during the prenatal period, affect postpartum behaviors. The current study seeks to describe women's narratives about their GDM experience and how these narratives guide their actions after birth.…”
Section: Introductionmentioning
confidence: 99%